Preliminary assessment of residual chlorine (Cl2) levels and contamination by chloramines in drinking water Arequipa city – 2015. - S S Flores Calla (2017)
Chlorine is a strong oxidizing agent and is the conventional chemical used in the disinfection process for water purification, reducing the risk of pathogenic infection. However, it may represent a chemical threat to human health due to waste and hazardous disinfection by-products formed as trihalomethanes, nitrosamines, chlorophenols, among others. This paper aims is to assess and monitor the concentration of free chlorine and chloramines in drinking water distributed in the city of Arequipa, to establish whether it is within the parameters set by the competent authority. Three monthly monitoring were performed in the distribution network of the three water treatment plants, performing the DPD spectrophotometric method, the experimental values to first order kinetic model were adjusted using the value of k = 0.0018 as decay constant. The values of free chlorine and chloramines, showed significant difference (p <0.05) in the months of monitoring, different water treatment plants and districts evaluated. It was concluded that the average values of free chlorine are within the parameters defined by the DIGESA and WHO. In addition chloramine concentration values are below the limit of 5 mg.L-1 that sets the international standard WHO.